2005
DOI: 10.1073/pnas.0503926102
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric inducible nitric oxide synthase localizes to peroxisomes in hepatocytes

Abstract: Hepatocytes are capable of repeated inducible NO synthase (iNOS) expression, which occurs under inflammatory and stress conditions. This iNOS expression regulates a number of cellular functions as well as cell viability. To better understand the posttranslational mechanisms that regulate the fate of iNOS in these cells, we characterized the iNOS distributed within peroxisomes. The selective permeabilization of membranes (plasma vs. peroxisomal) confirmed that there are cytosolic and peroxisomal pools of iNOS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Several NADP-dehydrogenases can produce NADPH (Corpas et al, 1998, while the presence of calmodulin in plant peroxisomes has been also demonstrated (Yang and Poovaiah, 2002) being both essential elements for this activity. These results could be important, particularly given that inducible NOS has also been reported in peroxisomes of rat hepatocytes (Stolz et al, 2002;Loughran et al, 2005).…”
Section: Pex12 and Pex13 Appear To Be Involved In The Peroxisomal Impmentioning
confidence: 97%
“…Several NADP-dehydrogenases can produce NADPH (Corpas et al, 1998, while the presence of calmodulin in plant peroxisomes has been also demonstrated (Yang and Poovaiah, 2002) being both essential elements for this activity. These results could be important, particularly given that inducible NOS has also been reported in peroxisomes of rat hepatocytes (Stolz et al, 2002;Loughran et al, 2005).…”
Section: Pex12 and Pex13 Appear To Be Involved In The Peroxisomal Impmentioning
confidence: 97%
“…Furthermore, even if a protein's sequence is not 100% identical to the canonical PTS sites, other enzymes have been described that target to the peroxisome with similar, but nonconventional PTS sequences; these include acetoacetyl-CoA thiolase, 39 alanine:glyoxylate aminotransferase, 40 isopentenyl diphosphate dimethylallyl diphosphate isomerase, 41 and iNOS. 27,42 In fact, very large protein oligomers lacking PTS motifs have been shown to piggy-back onto other conventional peroxisomal proteins and gain entry into the peroxisomal matrix in their native three-dimensional configuration. 43 Specifically, the primarily hydrophobic ␤-domain of vHL contains two critical hydrophilic residues (His-115 and Ser-111), which must hydrogen bond with either hydroxyproline or H 2 O molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of iNOS, a nonconventional peroxisomal enzyme in hepatocytes, the fraction of iNOS sequestered in peroxisomes is an inactive monomer, perhaps protecting the cell from incompetent enzyme. 42 On the other hand, phytanoyl Co-A hydroxylase is a classic PTS2-containing enzyme that leads to Refsum's disease if defective. 56 Not only is phytanoyl Co-A hydroxylase active in peroxisomes, it is actually a member of the same O 2 -, Fe 2ϩ -, and 2-oxogluterate-dependent oxygenase family as the HIF hydroxylases; therefore, within the peroxisomes there may exist a medium containing the co-factors necessary for PHD and FIH-1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Chaisson et al (2002) have shown that TNF-α activates NF-κB in many cells after intraperitoneal injection. Inducible nitric oxide synthase (iNOS) transcription is also induced by TNF-α and IL-6 through NF-κB activity (Shin et al, 2003); this occurs mainly in hepatocytes just after partial hepatectomy and before cell proliferation (Loughran et al, 2005). The most important growth factor involved in hepatocyte proliferation, HGF, signals through its receptor c-Met, a transmembrane tyrosine kinase protein product of the proto-oncogene with the same name (Huh et al, 2004).…”
Section: Nf-kb Promotes Liver Regenerationmentioning
confidence: 99%